Site as experiential playground: artistic research for a learning landscape - Kingery-Page, Katie; Melvin, Rebecca J. (My University, 2014)
The contemporary American schoolyard remains an under-utilized opportunity for experiential learning. Contemporary public schoolyards are often designed in response to perceptions of liability and a limited interpretation of child development. This paper examines a design proposal for an un-built, natural learning landscape through two lenses: epistemology and form. First, we propose that designers of school landscapes embrace artistic research as a humanities mode of knowledge. We illustrate an artistic research process using the design of an experiential schoolyard. Second, we present an un-built, primary grade schoolyard design as an exemplar for natural play and learning. Beginning with literature review of research on play and experiential learning, the proposed design layers child development, humanities, and landscape architectural knowledge to form a provisional understanding of how form and space may affect the child’s play experience.
Keywords: Landscape Architecture; Schoolyards; Landscapes of learning; Artistic research; Experiential schoolyard